Social Forestry - a Vital Production System - Shah, S. A. (Indian Forester, 1984)
Social Forestry, irrespective of the nomenclature used, aims at village self-sufficiency and self-reliance in regard to the forest based needs of the rural people. It should start with the rural poor and end with them. It deals primarily with poor people and poor lands. Social Forestry is a production system becanse it provides goods and services (largely non-monetised) needed by the rural people. It bas direct linkages with the Agricultural Production System and the Forest Production System. It helps increase agricultural production and productivity in a variety of ways. The maintenance of the Forest Production System is dependent upon the Social Forestry Production System. Thus, all these three major Production Systems are inlerlocked in the form of a triangle-Greea Triangle-which is complementary to the Red Triangle.